Cortisol Dysregulation Linking Metabolic and Psychological Disorders: A Cross-Sectional Study in Tripoli, Libya (Comprehensive Journal of Science, 2026)
Cortisol is a glucocorticoid hormone that regulates metabolism and psychological balance through activation of the stress response. This study aimed to explore the association between elevated cortisol levels and selected biochemical disorders including insulin resistance, Cushing’s syndrome, Addison’s disease, congenital adrenal hyperplasia, as well as psychological disorders such as depression and bipolar disorder. A total of 50 patients (aged 7–30 years, both sexes) were recruited from Al-Razi Psychiatric Hospital in Tripoli, Libya, between May 15 and July 30, 2025. Data were collected using a structured clinical questionnaire and analyzed using descriptive statistical methods in Microsoft Excel. The results showed that the highest prevalence was in the 21–30 age group (46%). Females were more affected by metabolic disorders (66%) compared to males (34%), while psychological disorders were also higher in females (58% vs. 42%). A clear association was observed between elevated cortisol and clinical symptoms such as obesity, anxiety, and depression. The study recommends adopting a healthy lifestyle, regular checkups, and cautious use of corticosteroids under medical supervision to reduce cortisol-related health risks.
Keywords: Cortisol, Metabolic disorders, Psychological disorders, Insulin resistance, Depression, Bipolar disorder, Obesity, Stress, Libya